(3GdCLhHI GdTGajI ef GdeSGFd GdeJfGajIs - (3CHh eMeO YHO Gddg Hf MeRI Hf SdjeGf Hf MeRI GdMSfj Gdjefj,J (B614 (3g` s
(3ChdgG (B:s
(3GdMeO ddg eSJMb GdMeO hQHg , GdPi LYd GdMeO Bdg ddTcQ , hGdTcQ SHHkG ddeRjO s
(3BNQgG (B:s
(3fSCd Gddg bdhHkG efbdHI eY GdMb hGdSdGe Ydjce hQMeg Gddg hGdMeO ddg hMOg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B8s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B83s
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI GdbGVi CMeO Hf Ydi GdCchY GdNGUI s
Keywords: (3abg GdePGgH GdCNQis